2016
DOI: 10.1186/s12906-016-1298-3
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of acupuncture for improving learning and memory ability in animals

Abstract: BackgroundMemory loss is the most prominent symptoms of brain aging, but there is currently no evidence-based treatment strategy. Acupuncture has been widely used in China and the effectiveness for improving learning and memory has been mentioned in previous studies. We conducted this systematic review and meta-analysis to evaluate the effectiveness of acupuncture for improving learning and memory in animal experiments.MethodsWe searched Pubmed, Embase, Ovid Medline(R), the China National Knowledge Infrastruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 26 publications
(27 reference statements)
1
13
0
Order By: Relevance
“…MWMT is a behavioral test in which rodents learn to find a platform hidden in the water [ 23 ]. It is mainly used to measure learning and memory of spatial orientation.…”
Section: Discussionmentioning
confidence: 99%
“…MWMT is a behavioral test in which rodents learn to find a platform hidden in the water [ 23 ]. It is mainly used to measure learning and memory of spatial orientation.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we used an MCAO model to investigate the mechanisms underlying the effects of electroacupuncture at Baihui and Shenting acupoints. In additional, Huang et al conducted a systematic review and found mild stimulation, which means the reinforcing method in TCM theory is adopted widely including improving functional impairment of post-stroke [ 35 ]. Shu et al found EA at GV26 acupoints and right sulcus auriculae posterior with the frequency of 2 and 20 Hz for 30 min, alternatively (disperse-dense waves), and intensity strong enough to only elicit slight twitches of the orofacial areas can significantly decreased neurological deficit scores and the volume of cerebral infarction, and relax the autophagy and apoptosis in cerebral ischemia reperfusion injury rats [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other possible effects of acupuncture may also be related to its ability to decrease the level of cytokines in the hippocampus [ 66 ], reverse the decreased acetylcholine neurotransmission [ 67 ], and reduce oxidative damage by increasing the activity of superoxide dismutase (SOD) [ 68 ]. The inhibition of nerve apoptosis and necrosis and suppression of oxidative stress are the main signaling pathways to be considered [ 69 ].…”
Section: Discussionmentioning
confidence: 99%